Analisis Komentar Netizen di Instagram pada Pemberitaan Pemecatan Shin Tae-Yong - Sarrah Kurnia Fadhillah; Yuli Santri Isma (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
The emergence of news about Shin Tae-Yong's dismissal became a trending topic on social media because it gave rise to various comments from Indonesian society. This news shocked the Indonesian people because Shin Tae-Yong is the Indonesian National Team Coach who is currently popular because he has succeeded in bringing about significant changes in the Garuda Team's performance. Therefore, this research analyzes how netizens' comments on the news of Shin Tae-Yong's dismissal via the social media Instagram are seen from the aspects of cognitive, affective and conative responses in communication. The type of research used is qualitative research with a library research approach. Data collection techniques are observation and documentation. The data analysis used is analysis of the content of comments on the news of Shin Tae-Yong's dismissal on Instagram. The results of the analysis show that the cognitive aspect that arises from reporting on Shin Tae-Yong is that netizens are more critical of the news circulating, netizens' understanding and knowledge about the incident of Shin Tae-Yong's dismissal increases so that netizens understand the reasons and background of the decision to dismiss. The affective aspect is that netizens feel sad, disappointed and angry with the decision to dismiss because Indonesian football under the leadership of Shin Tae-Yong is considered quite successful. From the conative aspect, netizens respond with protest comments which is one of the netizens' actions to participate in changing the situation through their opinions.